Pemberian Cairan Karbohidrat Elektrolit, Status Hidrasi dan Kelelahan pada Pekerja Wanita - Mardiana Mardiana; Apoina Kartini; Baju Widjasena (MEDIA MEDIKA INDONESIANA, 2012)
Carbohydrate electrolyte solution improve hydration status and decrease fatigue among women workersBackground: Heat exposure cause dehydration and fatigue if water intake is insufficient. Carbohydrate electrolyte drinks consumption maintans workers hydration status and prevent fatigue. Women workers at ironing department in garment industry are at risk of dehydration and fatigue because of the heat exposure.Objective: To determine the effect of carbohydrate electrolyte solution on hydration and fatigue status among women workers.Method: This quasy experiment was conducted in pre post test control group design. Population of this study was women workersaged 18-35 years in ironing department of garment industry. Thirty-three subjects were selected by inclution criteria. Subjects were given three treatments, without intervention, drink water and carbohydrate electrolyte solution. Body weight and fatigue of the subjects were measured on the third, fourth, and fifth intervention days before and after each treatment. Body weight was measuredusing digital scales. Fatigue was measured by reaction timer to flash light. Data were analyzed using paired t test, Wilcoxon test, and Ancova.Result: Body weight decreased 0.1?0.2 kg after work without intervention and drinking water, while increased body weight of 0.1?0.1 kg after given carbohydrate electrolyte. Reaction timed to flash light decreased 12.2?49.0 milliseconds after given carbohydrate electrolyte solution increased 14.9?62.3 and 26.4?33.8 milliseconds after drinking water and without intervention respectively. Drinking carbohydrate electrolyte solution improved hydration status and decreased fatigue status before and aftercontrolled for energy and fluid intake, vitamin B1 and B6 intake.Conclusion: Carbohydrate-electrolyte solution improved the hydration status and decreased fatigue among women workers.Keywords: Carbohydrate-electrolyte solution, hydration status, fatigue, women workers ABSTRAKLatar belakang: Paparan panas selama bekerja dapat menyebabkan dehidrasi dan kelelahan jika asupan cairan tidak cukup. Penambahan cairan karbohidrat elektrolit selama bekerja diduga dapat mencegah dehidrasi dan kelelahan. Pekerja wanita di bagian ironing perusahaan garmen terpapar panas sehingga berisiko dehidrasi dan kelelahan. Tujuan penelitian ini untuk mengetahui pengaruh pemberian cairan karbohidrat elektrolit terhadap status hidrasi dan kelelahan pada pekerja wanita.Metode: Desain penelitian nonrandomized pre-post test control group design. Populasi adalah pekerja wanita perusahaan garmen berusia 18-35 tahun di bagian ironing. Subyek berjumlah 33 orang yang dipilih berdasarkan kriteria inklusi. Subyek mendapat tiga perlakuan, yaitu tanpa intervensi, pemberian air minum dan karbohidrat elektrolit. Subyek diukur berat badan dan kelelahan sebelum dan setelah bekerja selama tiga hari berturut-turut untuk setiap perlakuan. Pengukuran berat badan menggunakan timbangan injak digital. Kelelahan diukur melalui kecepatan dalam merespon cahaya dengan menggunakan alat reaction timer. Data dianalisis menggunakan paired t test, Wilcoxon, repeated measure, dan uji Ancova.Hasil: Pada kondisi tanpa intervensi dan pemberian air minum terjadi penurunan berat badan (0,1?0,1 kg) setelah bekerja, sedangkan pada pemberian karbohidrat elektrolit terjadi peningkatan berat badan sebesar 0,1?0,2 kg. Waktu reaksi rangsang cahaya menurun sebesar 12,2?49,0 millidetik setelah pemberian karbohidrat elektrolit dan meningkat sebesar 26,4?33,8 millidetik pada kondisi tanpa intervensi serta 14,9?62,3 millidetik pada pemberian air minum. Pemberian cairan karbohidrat elektrolit memperbaiki status hidrasi sebelum dan setelah dikontrol dengan asupan energi dan cairan serta menurunkan kelelahan sebelum dan setelah dikontrol dengan asupan energi, cairan, vitamin B1, dan vitamin B6. Simpulan: Pemberian cairan karbohidrat elektrolit dapat memperbaiki status hidrasi dan menurunkan kelelahan